Specialist service for the provision of opthalmic benefit (circular) - Harwood, E. G.
1929-01 1929 1920s 8 pages The Board which has been set up to control the organisation is for the time being composed of representatives of the medical profession and dispensing opticians only, but as will be seen from the appendix it is proposed as soon as Approved Societies generally are participants, to invite two representatives of Approved Societies and a representative of the Ministry of Health to take seats on the Board. I am to request that you will be good enough to inform me at an early date whether you wish to avail yourself of the service in the localities mentioned in order that the necessary arrangements may be made. Yours faithfully, E.G. HARWOOD. 3 292/841.4/1/58